REALISM IN KAMALA MARKANDAYA’S “NECTAR IN A SIEVE” (International Journal of Food and Nutritional Sciences, 2022)
Kamala Markandaya was born in 1924 into an affluent and aristocratic Brahmin family of Mysore, South India. Her family has been closely associated with a princely state of India. She is linked with the Dewan Purnaiya family of Mysore. Her original name was Kamal Purnaiya. As she was born into a rich family and belonged to the westernized upper class society of India, she was given a thoroughly western upbringing. She could not remain peacefully because of the frequent tranfers of her father who was in the railways. Though it was quite wearisome and worrisome, it proved to be a boon affording opportunities to learn more resulting in adding new dimensions in the vast store of her Knowledge.